2017
DOI: 10.1016/j.jneumeth.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the ferret as a gyrencephalic animal model of traumatic brain injury: Optimization of controlled cortical impact procedures

Abstract: We optimized ferret CCI surgery for consistent injury placement. The ferret is an excellent animal model to investigate pathophysiological and behavioral changes associated with TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 72 publications
1
37
0
Order By: Relevance
“…This agrees with several studies of TBI in humans, where microglia do not show immediate increases in the white matter but, instead, demonstrate long-term changes in density persisting from 2 weeks to a year post injury (Johnson et al, 2013;Smith et al, 2013). The morphology of the microglia did not become amoeboid in the animals we studied here with a mild CCI, although in our previous study that included a more severe injury, the IBA1 immunoreactivity exhibited amoeboid morphology (Schwerin et al, 2017). In the earlier study, we also observed microglia with a rodlike morphology after severe injury.…”
Section: Morphologic Changes Of Microglial Reactivity In White Mattersupporting
confidence: 92%
See 4 more Smart Citations
“…This agrees with several studies of TBI in humans, where microglia do not show immediate increases in the white matter but, instead, demonstrate long-term changes in density persisting from 2 weeks to a year post injury (Johnson et al, 2013;Smith et al, 2013). The morphology of the microglia did not become amoeboid in the animals we studied here with a mild CCI, although in our previous study that included a more severe injury, the IBA1 immunoreactivity exhibited amoeboid morphology (Schwerin et al, 2017). In the earlier study, we also observed microglia with a rodlike morphology after severe injury.…”
Section: Morphologic Changes Of Microglial Reactivity In White Mattersupporting
confidence: 92%
“…immediately after the open field test. We tested NOR in the ferret using vinyl/rubber/plastic dog toys (see Table 1) as described in Schwerin et al (2017). For the familiarization phase, we secured two identical objects in opposite corners of the open field apparatus and then let the ferret investigate them for 10 min.…”
Section: Novel Object Recognitionmentioning
confidence: 99%
See 3 more Smart Citations